Contribution of xylan to the brightness development and stability in the final ECF bleaching of eucalypt (Eucalyptus globulus Labill.) kraft pulp - Loureiro, Pedro E. G. (2017)
Xylans isolated from eucalypt kraft pulps have been characterized by modern analytical methods. The pulps were partially bleached (DEOPD) and fully bleached with either a final ClO2 (DEOPDD) or an alkaline H2O2 (DEOPDP) bleaching stage. Alternatively, xylan isolated from the DEOPD pulp was treated with ClO2 or with H2O2 under the same conditions as pulps in a final bleaching stage and were further characterized. 1 H nuclear magnetic resonance, size exclusion chromatography, UV-vis spectroscopy in cadoxen solution, and UV-resonance Raman spectroscopy were applied as analytical methods. The final ClO2 stage generated new unsaturated moieties in xylan, whereas H2O2 was very effective in the removal of xylan-related chromophores. The role of xylan to the delay of brightness development in the final ClO2 stage was highlighted by means of a pretreatment with xylanase Pulpzyme HC before the final bleaching stage. By this approach, the final bleachability of the pulp was boosted and the brightness stability of the fully bleached pulp was improved.